Assessing the deflection behaviour of mechanical and insulated rail joints using finite element analysis. (October 2018) - Gallou, M; Frost, M; El-Hamalawi, A; Hardwick, C
Rail joints constitute a weak component in the railway system. In this paper, three-dimensional finite element analyses are carried out to study the structural deflection performance of rail joints under a fatigue static test through vertical stiffness assessment. Four different types of four-bolted joints are investigated under a dynamically enhanced static load including a glued insulated rail joint, a dry encapsulated insulated rail joint, a dry non-glued insulated rail joint and a mechanical rail joint. The analysis focused on the accurate simulation of the contact types between the interfaces of rail joint components, namely the rail, fishplate faces, bolts and insulating materials. It also focused on the effect of the elastic supporting structure of the joint with regard to the overall joint deflection. The effect of bolt pre-tension is included in the model. The vertical displacement of insulated rail joints is measured experimentally by dial gauges and a video technique in both laboratory and field settings. The numerical modelling investigated the effect of different contact types on the interfaces of the rail joint components during the performance of fishplates, and of the rail in the vicinity of the rail joint under a given support condition. The vertical displacement of the rail joint was presented and assessed against specified limits of endurance tests and field-measured deflection values that validate the model. Stress distribution in the fishplates was presented that could allow the calculation, through a stress-life approach, the fatigue life of the fishplates and, consequently, of the joints due to repeated wheel passage. A comparison of the performance of the aforementioned rail joint types is included. The results indicate that this finite element model can be routinely used in industries, as it was used in the UK Rail industry study, to allow designers to optimize the life expectancy of insulated rail joints.